2021
DOI: 10.1002/spy2.181
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of network security situation awareness based on an improved model combined with neural network

Abstract: People always pay attention to the security of the network. This paper mainly analyzed the problem of network security situation prediction (NSSP). The radial basis function neural network was improved by the particle swarm optimization algorithm, and a modified particle swarm optimization‐radial basis function algorithm was obtained, which was used as the prediction model. Then, the data from National Internet Emergency Center were used as the experimental data, and the modified particle swarm optimization‐ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Yuan (2021) [5] developed an improved RBF algorithm and particle swarm optimization (PSO) algorithm, which was successfully applied to NSSP problems and improved the accuracy of the network security situation prediction model, making an important contribution to protecting network security.…”
Section: Related Workmentioning
confidence: 99%
“…Yuan (2021) [5] developed an improved RBF algorithm and particle swarm optimization (PSO) algorithm, which was successfully applied to NSSP problems and improved the accuracy of the network security situation prediction model, making an important contribution to protecting network security.…”
Section: Related Workmentioning
confidence: 99%
“…Wang verified the advantages of RBF neural network through comparative analysis, realized the optimization of RBF and BPNN models, and proved the reliability of neural network method in security situation prediction, which was conducive to the further application of neural network. [5] designed the improved Radial Basis Function (RBF) algorithm and Particle Swarm Optimization (PSO) algorithm and verified the effectiveness of the algorithm to solve the NSSP problem through experimental analysis, which made a contribution to the better realization of network security. [6] designed a backpropagation neural network (BPNN) model to evaluate the situation value.…”
Section: Related Workmentioning
confidence: 99%
“…The literature [17] compared several network security posture prediction methods and concluded that the particle swarm optimization (PSO) algorithm optimized radial basis (RBF) neural network has better performance. The literature [18] similarly proposed an improved PSO algorithm to optimize RBF neural networks for situational prediction.…”
Section: Introductionmentioning
confidence: 99%